CHEMICAL CATALYTIC AND BIOCATALYTIC PROCESS OF CLOVE OIL DERIVATIVES REVIEW - Silvester Tursiloadi; Nina Artanti; Anny Sulaswatty (Jurnal Kimia Terapan Indonesia, 2015)
In 2011, Indonesian clove oil supply reached about 75 % (4,500 of 6,000 tons) of the world market. Utilization of clove oil and clove oil derivatives in aromatic chemical industry primarily as a mixture or additive of fragrances in the daily consumed product, such as perfumes, skin care products, deodorant, soap, shampoo, detergent, besides it is also used as an ingredient in the production of synthetic vanilla. The content of eugenol as the main compound in the essential oil in the clove flower, flower stalk and leaf have a range of 90-95 %, 83-95 % and 82-87 % respectively. The compounds content in clove oil is divided into two categories, phenolics (eugenol) and non-phenolic (beta-caryophyllene) that can be derivatized with various chemocatalytic and biocatalytic processes. Separation of the compounds in clove oil can be conducted by adding NaOH with repeated distillation. This process produces two layers product, the first layer contains eugenol and NaOH, while the second layer contains beta-caryophyllene. Derivatization of eugenol are conducted to produce various products such as vanilla, eugenyl ether, methyl ether eugenyl, eugenyl ethyl ether, eugenyl acetate, eugenyl cinnamate, dimmer eugenol and eugenyl benzoate, whereas derivatization of beta-caryophyllene are conducted to produce products such as caryophyllene oxide, kobusan, glycols, alcohols caryophyllene, β-caryolanylformate and kovanilformate, klovanildiformate, caryophyllene ketol. Biocatalysis or biotransformation can be defined as the use of biological systems (intact cells, cell extracts or isolated enzymes) to catalyze the conversion of a compound into another. Besides the common chemocatalysis system for derivatization of clove oil and clove oil compound such as eugenol into other compounds some biocatalysis systems were also described in this paper.Keywords: Clove oil, eugenol, beta-caryophyllene, derivatization, chemical catalysis, biocatalysis